2016
DOI: 10.3390/dj4010004
|View full text |Cite
|
Sign up to set email alerts
|

Infection and Pulp Regeneration

Abstract: The regeneration of the pulp-dentin complex has been a great challenge to both scientists and clinicians. Previous work has shown that the presence of prior infection may influence the characteristics of tissues formed in the root canal space after regenerative endodontic treatment. The formation of ectopic tissues such as periodontal ligament, bone, and cementum has been observed in the root canal space of immature necrotic teeth with apical periodontitis, while the regeneration of dentin and pulp has been id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 73 publications
(119 reference statements)
1
33
0
1
Order By: Relevance
“…This finding was in agreement with Kim who reported that cases seen after a long post‐traumatic period showed more complications than those presented within a short period. This could be explained that although it was difficult or impossible to determine the presence of viable cells clinically or to assess the ability of these cells to survive and differentiate, the duration of the infection appears to be an indicator of that potential …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was in agreement with Kim who reported that cases seen after a long post‐traumatic period showed more complications than those presented within a short period. This could be explained that although it was difficult or impossible to determine the presence of viable cells clinically or to assess the ability of these cells to survive and differentiate, the duration of the infection appears to be an indicator of that potential …”
Section: Discussionsupporting
confidence: 93%
“…One case in the MTA group was identified as a clinical failure due to the presence of pain on biting and pain on percussion at 12‐month follow‐up. As postulated by several reports, the failure might be due to the increased bacterial growth in the dentinal tubules, accessory canals or the biofilm on the canal wall, and thus, the canal became re‐infected and caused tissue destruction.…”
Section: Discussionmentioning
confidence: 94%
“…Journal of Endodontics 43, 2034-40. Zhujiang A, Kim SG (2016) Regenerative endodontic treatment of an immature necrotic molar with arrested root development using recombinant human platelet-derived growth factor: a case report. Journal of Endodontics 42, 72-5.…”
Section: Resultsmentioning
confidence: 99%
“…However, if infection is not under control, not only regeneration but also repair will not occur (Myers & Fountain 1974). The presence of prior infection could negatively affect the process of pulp tissue regeneration by damaging tissue forming cells as well as stem cells in the periapical tissues (Kim 2016). This is supported by the histological findings from animal studies and human case reports that tissues formed in the root canal space in the previously infected root canals were not the pulp-dentine complex but of periodontal origin such as bone, cementum and periodontal ligament (Wang et al 2010, Becerra et al 2014, Lei et al 2015, Saoud et al 2015.…”
Section: Root Canal Disinfectionmentioning
confidence: 99%
See 1 more Smart Citation